Short - and middle-latency waves Auditory evoked potential recordings in children with history of neonatal hypoxicischemic encephalopathy - Portillo Vallenas, Roberto (2001)
OBJECTIVE: To assess short- and middle-latency waves evoked potentials in children with history of neonatal hypoxic ischemic encephalopaty (HIE). SETTING: Guillermo Almenara Irigoyen Hospital Neurophysiology Unit, Lima - Peru. MATERIAL AND METHODS: Auditory evoked potential recordings of short (BAEP) and middle (MAEP) latency waves in seventy-eight children, aged 0 to 4 year-old, with history of HIE were performed. Children were classified according to the HIE degree. RESULTS: BAEPs were present in 68% of the patients, and there was not differences of statistical significance between groups. MAEPs were absent in 77% of the patients, especially in those who showed moderate and severe grades of HIE (90%) (p <0,005). CONCLUSION: It is possible that the moderate or severe HIE’s damage at the corticoreticulothalamocortical path produces absence of MAEP waves.